Penerapan keterampilan bertanya guru untuk meningkatkan keaktifan peserta didik di kelas V sekolah dasar - Hemas Putri Pradana; Hasan Mahfud; Supianto Supianto (Didaktika Dwija Indria, 2024)
The purpose of this research are (1) To increase the activity of students through the application of the questioning skills of the fifth grade teacher at SDN Sentul, (2) To find out the application of the teacher's questioning skills that can increase the activity of students in class, (3) To find obstacles and solutions in application of teacher's questioning skills to increase student activity. The research approach uses a qualitative approach with Classroom Action Research (CAR) methods. The subjects of this study were 18 students in class V, and a teacher at grade V SDN Sentul. This study uses observation techniques, interviews, questionnaires, and documentation. Data analysis adopts data analysis by Sukardi with 6 steps with the steps of collecting data, displaying data, coding, reducing data, conducting verification and interpretation, drawing conclusions. The results of the research show that the application of the teacher's questioning skills with learning steps is observing the learning videos; question and answer; discussion; presentation of results; and reinforcement shows an increase in activity in each cycle. This is evidenced in the pre-action activity of 41,14%, cycle 1 of 61,66%, cycle 2 of 70,58% and cycle 3 of 81,25%.